2020
DOI: 10.2478/helm-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Copro-prevalence and risk factor assessment of gastrointestinal parasitism in Indian domestic pigs

Abstract: SummaryThe aim of the present study was to determine copro-prevalence of gastrointestinal parasites and their associated potential risk factors in pigs of Punjab (India). A total of 839 faecal samples were collected from pigs of all age group and sex from different agro-climatic zones of Punjab covering all seasons and subjected to qualitative and quantitative examination. Among the samples examined, 28.4 % were positive for gastrointestinal parasites and their respective prevalences were Ascaris suum (11.1 %)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
6
10
0
Order By: Relevance
“…Finishing pigs need a clean breeding environment to reduce their contact with coccidia oocysts. Our research revealed that the point estimates of coccidia prevalence were slightly higher in sows than in boars [ 17 , 42 ], but the differences were not significant ( P < 0.05), as reported elsewhere [ 42 ]. Schwarz et al noted that sows might confer piglet resistance to C. suis through lactation [ 41 ]; however, another study pointed out that coccidiosis infection in piglets might originate from oocysts introduced into the farrowing bed by the sow [ 59 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Finishing pigs need a clean breeding environment to reduce their contact with coccidia oocysts. Our research revealed that the point estimates of coccidia prevalence were slightly higher in sows than in boars [ 17 , 42 ], but the differences were not significant ( P < 0.05), as reported elsewhere [ 42 ]. Schwarz et al noted that sows might confer piglet resistance to C. suis through lactation [ 41 ]; however, another study pointed out that coccidiosis infection in piglets might originate from oocysts introduced into the farrowing bed by the sow [ 59 ].…”
Section: Discussionsupporting
confidence: 76%
“…In the season subgroups, the prevalence of coccidia in the spring and summer was twofold higher than that in autumn and winter, which indicates that coccidia infection is related to temperature and humidity. Coccidia infection might occur throughout the year, but the incidence of coccidia in pigs is significantly higher under conditions of high temperature and high rainfall [ 12 , 42 ]. Based on these findings, deworming procedures should be strengthened during the spring and summer.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the household rears two to ten locally available indigenous breed Sus domesticus (“Chwanche” in the Nepali language; Figure 2) under scavenging management (Pant, 2017) at the backyard of their house (Associate Professor Dr. Nirajan Bhattarai, Department of Animal Breeding and Biotechnology, Faculty of Animal Science, Veterinary Science and Fisheries, Agriculture and Forestry University, Rampur, Chitwan, Nepal: personal communications). Pigs were categorized into suckling and weaner (piglets <4 months), growers (4–8 months), and adults (>8 months) groups as previously described (Sharma et al., 2020). The inclusion criteria of the survey farms were accessibility of the farms and voluntary participation of the pig farmers.…”
Section: Methodsmentioning
confidence: 99%
“…Parasitism exists widely in fauna and flora. 28,29 A parasitic relationship can be considered as a mechanism in which the host is the output link and the parasite has a passive DOF. Thus, the DOF of a mechanism can be analyzed by considering it as a tree-rattan parasitic relationship or as a tree-rattan mechanism.…”
Section: Tree-rattan Mechanismmentioning
confidence: 99%